Resistance to Antibiotics, Biocides, Preservatives and Metals in Bacteria Isolated from Seafoods: Co-Selection of Strains Resistant or Tolerant to Different Classes of Compounds - Romero, José L.; Grande Burgos, María J.; Pérez-Pulido, Rubén; Gálvez, Antonio; Lucas, Rosario (Frontiers in Microbiology, 2017)
Multi-drug resistant bacteria (particularly those producing extended-spectrum β-lactamases) have become a major health concern. The continued exposure to antibiotics, biocides, chemical preservatives and metals in different settings such as the food chain or in the environment may result in development of multiple resistance or co-resistance. The aim of the present study was to determine multiple resistances (biocides, antibiotics, chemical preservatives, phenolic compounds and metals) in bacterial isolates from seafoods. A 75.86% of the 87 isolates studied were resistant to at least one antibiotic or one biocide, and 6.90% were multiply resistant to at least three biocides and at least three antibiotics. Significant (P < 0.05) moderate or strong positive correlations were detected between tolerances to biocides, between antibiotics, and between antibiotics with biocides and other antimicrobials. A sub-set of 30 isolates selected according to antimicrobial resistance profile and food type were identified by 16S rDNA sequencing and tested for copper and zinc tolerance. Then, the genetic determinants for biocide and metal tolerance and antibiotic resistance were investigated. The selected isolates were identified as Pseudomonas (63.33%), Acinetobacter (13.33%), Aeromonas (13.33%), Shewanella, Proteus and Listeria (one isolate each). Antibiotic resistance determinants detected included sul1 (43.33% of tested isolates), sul2 (6.66%), blaTEM (16.66%), blaCTX-M (16.66%), blaPSE (10.00%), blaIMP (3.33%), blaNDM-1 (3.33%), floR (16.66%), aadA1 (20.0%) and aac(6’)-Ib (16.66%). The only biocide resistance determinant detected among the selected isolates was qacEΔ1 (10.00%). A 23.30 of the selected isolates were able to grow on media containing 32 mM copper sulfate, and 46.60% on 8 mM zinc chloride. The metal resistance genes pcoA/copA, pcoR and chrB were detected in 36.66%, 6.66% and 13.33% of selected isolates, respectively. Twelve isolates tested positive for both metal and antibiotic resistance genes, including one isolate positive for the carbapenemase gene blaNDM-1 and for pcoA/copA. These results suggest that exposure to metals could co-select for antibiotic resistance and also highlight the potential of bacteria on seafoods to be involved in the transmission of antimicrobial resistance genes.